Empowering Cultural Heritage Through North Sumatran Batik for Nihongo Partners from Japan and Local Indonesian Communities - Kazumi, Inami; Muzakkir, Muzakkir; Marpaung, Watni; Wahyuni, Sri; Reza, Muhammad (Jurnal Abdi Mas Adzkia, 2025)
This community service project aimed to strengthen cultural identity through the introduction and practice of North Sumatran batik among Japanese Nihongo Partners and local Indonesian participants. The program addressed the growing need for cross-cultural understanding and cultural preservation in the era of globalization. The method employed was participatory and experiential learning, which included demonstrations, guided batik workshops, and cultural dialogues. Participants were introduced to the history, techniques, and symbolic meanings of batik patterns unique to North Sumatra. The activity not only enhanced participants' technical skills in traditional textile production but also deepened their appreciation for Indonesian heritage. Japanese participants, in particular, reported meaningful cultural insights and creative satisfaction through hands-on engagement. The outcomes of the program included increased intercultural awareness, the preservation of local batik knowledge, and opportunities for community-based entrepreneurship. Furthermore, the initiative supported environmental sustainability by promoting eco-friendly dyeing methods. In conclusion, the program proved effective in bridging cultural gaps and inspiring mutual respect through shared creative experiences. It also contributed to the promotion of batik as a symbol of cultural diplomacy and sustainable heritage education.